"Battle of narratives" in Ukraine's modern media space - Snytko , Olena; Hrechka , Stanislav (Current issues of Ukrainian linguistics: theory and practice, 2022)
The paper explores strategic communications in Ukraine's media space. Strategic communications as a system of multi-vector interaction with society have proven to be connected with a range of relevant and socially important issues, acting as the most effective technology in building the information defence amid intense hybrid aggression and ensuring the country's cognitive resilience. Typical anti-Ukrainian narratives undermine the main political reference points and affect the society's cognitive stability. The analysis of narrative realizations confirms that anti-Ukrainian narratives belong to post-truth. These narratives reflect the chaotization of world image: irrationality, emotionality, evaluation, expressiveness, and persuasiveness replace objectivity and rationality. The study determines the main features of strategic narratives and establishes the grand narrative in the strategic communications system. The paper claims a "battle of narratives" representing a struggle of different behavioural models exists in Ukraine's media space. All anti-Ukrainian narratives undermine the central Ukrainian narrative (or grand narrative), the identity narrative, while the majority of pro-Ukrainian narratives promote the idea of the Ukrainian people as a nation. An effective strategic narrative inevitably engenders a counter-narrative that aims at deconstructing or delegitimizing the previous narrative's (or its variants') effect on the target audience. A counter-narrative creation mechanism does not entail symmetry; its objective is to reprogram the call to action and block the recipients' motivational potential.
Keywords: strategic communications, strategic narrative, narrative variability, counter-narrative and its asymmetric structure, battle of narratives.